Occurrence of pressure-forced meteotsunami events in the eastern Yellow Sea during 2010–2019 - M.-S. Kim (Copernicus Publications, 2021)
This study examined the occurrence of meteotsunamis in the eastern Yellow Sea and the conceptual framework of a monitoring/warning system. Using 1 min intervals of mean-sea-level pressure and sea-level observations from 89 meteorological stations and 16 tide gauges between 2010 and 2019, a total of 42 pressure-forced meteotsunami events were classified. Most meteotsunamis (71 %) displayed a distinct seasonal pattern occurring from March to June, and intense meteotsunamis typically occurred at harbor tide gauges. The occurrence characteristics of the meteotsunamis were examined to improve the meteotsunami monitoring/warning system. Air pressure disturbances with speeds of 11–26 m s−1 and NNW–SW directions were conducive to meteotsunami generation. Most meteotsunamis (88 %), as well as strong meteotsunamis with a wave height exceeding 40 cm (19 %), had dominant period bands of less than 30 min, containing the resonant periods of harbors in the eastern Yellow Sea. Thus, the eastern Yellow Sea is a harbor-meteotsunami-dominated environment, characterized by frequent meteotsunami occurrences and local amplification in multiple harbors. This study can provide practical guidance on operation periods, potential hot spots, and risk levels to monitoring/warning system operators in the eastern Yellow Sea.